HUBUNGAN GAYA KEPEMIMPINAN DEMOKRATIS DENGAN SEMANGAT KERJA PEGAWAI PT. TASPEN (PERSERO) KC PEKANBARU - Mastura, Khoirul; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study was to determine the relationship with the democratic leadership style on employee morale PT. Taspen (Persero) KC Pekanbaru. This study is located in the PT. Taspen (Persero) The KC Pekanbaru is located in Pekanbaru 317 Jalan Sudirman. The study population was all employees in the PT. Taspen (Persero) KC Pekanbaru, amounting to 24 people. Analysis of the data in this study using SPSS version 16. Sampling technique used is the method of census data and testing techniques used in this study include the validity test, reliability test, the product moment correlation coefficient and t-test to test and prove the research hypothesis.The analysis showed that the democratic leadership style has a significant relationship with employee morale at. Taspen (Persero) KC Pekanbaru. Based on the results obtained r value (correlation coefficient) of 0.885% means that 88.5% variable employee morale PT. Taspen (Persero) KC Pekanbaru associated with a democratic leadership style. The results of hypothesis testing showed that the t-test is greater than t-table which means Ha accepted.Keywords: Leadership styles, Motivation, Work Discipline and Employee Performance